(Hf0.25Zr0.25Sn0.25Ti0.25)O2 high‐entropy ceramics and their microwave dielectric characteristics. Issue 11 (14th July 2022) - Ding, Yi Han; Liu, Lu; Guo, Rui Ze; Li, Lei; Chen, Xiang Ming
Abstract: (Hf0.25 Zr0.25 Sn0.25 Ti0.25 )O2 high‐entropy ceramics were designed and prepared, and their microwave dielectric characteristics were investigated together with the microstructures. The single‐phase structure in space group Pbcn was determined, and the excellent microwave dielectric characteristics were achieved in the present ceramics: εr = 25.6, Qf = 74 600 GHz at 6.5 GHz and τf = −47 ppm/°C. The significant improvement of Qf value was achieved with a prolonged sintering, where the dielectric constant increased slightly while the negative τf decreased in the absolute value at first and then turned to increase. The variation tendency of microwave dielectric characteristics was deeply linked with the microstructure homogeneity, and the introduction of Hf and Sn elements to create the high‐entropy ceramics resulted in the disordered state, and finally led to the improved Qf value . The present work provided an effective approach to achieve enhanced Qf value in microwave dielectric ceramics.